Five years of Lithuanian school for young mathematicians - Apynis, Antanas; Stankus, Eugenijus; Šinkūnas, Juozas (Lietuvos matematikos rinkinys, 2004)
The activities of Lithuanian School for Young Mathematicians during the period of last five years are analyzed.